Prescription trends of antiseizure medications before and during the COVID-19 pandemic - Lavu, Alekhya; Janzen, Donica; Aboulatta, Laila; Peymani, Payam; Haidar, Lara; Desrochers, Brianne; Alessi-Severini, Silvia; Eltonsy, Sherif (Frontiers in Neurology, 2023)
Introduction: Given the lack of evidence on how the COVID-19 pandemic impacted antiseizure medications (ASMs) use, we examined the trends of ASMs before and during COVID-19. Methods: We conducted a population-based study using provincial-level health databases from Manitoba, Canada, between June 1, 2016, and March 1, 2021. We used interrupted time series autoregressive models to examine changes in the prevalence and incidence of ASMs prescription rates associated with COVID-19 public health restrictions. Results: Among prevalent users, COVID-19 pandemic led to a significant increase in new generation ASMs with a percentage change of 0.09% (p = 0.03) and a significant decrease in incidence use of all ASMs with a percentage change of -4.35% (p = 0.04). Significant trend changes were observed in the prevalent use of new generation ASMs (p = 0.04), and incidence use of all (p = 0.04) and new generation ASMs (p = 0.02). Conclusion: With the introduction of public health measures during COVID-19, small but significant changes in the incident and prevalent use of ASMs prescriptions were observed. Further studies are needed to examine if barriers to medications' access was associated with potential deterioration in seizure control among patients.